Pengelolaan Sampah Berbasis Pelibatan Masyarakat Di Kelurahan Menteng Kecamatan Jekan Raya Kota Palangka Raya Provinsi Kalimantan Tengah - Siska Dina Mariana; Rita Rahmaniati (Pencerah Publik, 2021)
This study aims to provide an effort to provide an overview of how waste management is based on community involvement in Menteng Village, Jekan Raya District, Palangka Raya City, Central Kalimantan Province. The type of research used is qualitative research methods. Sources of data in this study consisted of primary data and secondary data. The primary data is the Solid Waste Management Section at the Palangkaraya City Residential and Settlement Service, UPT. Integrated Waste Management of Jekan Raya Region II District, Community in Menteng Village, Jekan Raya District, Palangkaraya City. While the secondary data source is Palangkaraya City Regional Regulation Number 1 of 2017 concerning Waste Management and Cleanliness. Based on the results of the research, it can be explained that Waste Management Based on Community Involvement in Menteng Village, Jekan Raya District, Palangka Raya City, Central Kalimantan Province, in general this has not been maximized because (1) the implementation of socialization (banner / banner) is not maximal. Number 1 of 2017 (2) Guidance and supervision were still lacking, only at the beginning of the Regional Regulation (3) The role of the public and private sector still needs to be improved to optimize waste management in Menteng Village, Jekan Raya District, Palangka Raya City.